Tourism community detection: A space of flows perspective. (December 2022) - Xu, Dong; Zhang, Jin-He; Huang, Zhenfang; Zhou, Yepeng; Fan, Qingyu
Abstract: The "space of flows" theory, emphasizing the exchange of information and movement of matters at the time-space level, provides a new scientific perspective for deepening the study of interactive networks of tourism destinations. By linking tourism flow data with network scientific approaches, this study identifies several tourism communities, sheds light on their internal relations and then explores the driving factors. The results show that the Yangtze River Delta urban agglomeration includes 7 actual and 6 potential tourism communities. There are significant differences in the characteristics of tourism flow within and across these communities, indicating that an accurate prediction of regional tourism demand should pay attention to the spatiotemporal attributes of flow elements. Moreover, the roles of informatization and government behavior in forming destination networks should be highlighted among the driving factors of tourism communities. The implications of tourism community detection for integrated development of regional tourism are finally discussed.